Evaluating the efficacy of cryopreservation media for the preservation and short-term storage of human dermal fibroblast - Tithteeya Rattanachot,; Nur Rasyidah Hazimah Mohd Rosdi,; Nusaibah Sallehuddin,; Fauzi Mh Busra,; Manira Maarof, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Cryopreservation is a vital process for long-term preservation of cells without compromising their viability and functionality. Continuous cell culturing can lead to reduction in cell viability, higher risk of contamination, and increased reagent consumption. Optimizing short-term storage is essential to minimize cell damage and enhance cell adaptability for applications requiring brief storage duration. This study evaluates the effects of short-term storage on human dermal fibroblasts cryopreserved in different cryopreservation media. Redundant skin samples were obtained from surgeries with patient consent, processed, and sub-cultured to passage three (P3). Confluent cells were trypsinised and cryopreserved in three cryopreservation media: Foetal bovine serum with 10% dimethyl sulfoxide (FBS+10%DMSO), CryoStor10 (CS10), and cryo freezing serum-free media (CF-SFM). Cells were stored at -80 °C for 7 days, 14 days, and 1 month. Fibroblasts maintained their spindle-shaped, elongated morphology across all groups post-storage. The total number of live cells slightly decreased after 1 month, but no significant differences were found between the groups. Cell viability in CS10 after 1 month was significantly lower compared to the other storage durations, while no significant differences were observed in the other two media groups. Immunocytochemistry showed positive collagen type I (Col-1) and Ki67 expression at all storage durations. These findings suggest that fibroblasts retain their characteristics after short-term storage at -80 °C in different cryopreservation media. However, further studies are needed to examine the impact of long-term storage on other cell types.